2018
DOI: 10.1371/journal.pone.0199604
|View full text |Cite
|
Sign up to set email alerts
|

Groove in drum patterns as a function of both rhythmic properties and listeners’ attitudes

Abstract: Music psychology defines groove as humans’ pleasureable urge to move their body in synchrony with music. Past research has found that rhythmic syncopation, event density, beat salience, and rhythmic variability are positively associated with groove. This exploratory study investigates the groove effect of 248 reconstructed drum patterns from different popular music styles (pop, rock, funk, heavy metal, rock’n’roll, hip hop, soul, R&B). It aims at identifying factors that might be relevant for groove and worth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
87
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(116 citation statements)
references
References 93 publications
(138 reference statements)
12
87
3
Order By: Relevance
“…Musical training may lead to an increased awareness and appreciation of syncopation and its effect on the desire to move. For example, musicians have been shown to use syncopation intentionally to convey groove [15] and musical expertise has been positively linked with the effect of syncopation on groove ratings [25]. Musical training may lead to more developed internal models that lead to stronger rhythmic expectations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Musical training may lead to an increased awareness and appreciation of syncopation and its effect on the desire to move. For example, musicians have been shown to use syncopation intentionally to convey groove [15] and musical expertise has been positively linked with the effect of syncopation on groove ratings [25]. Musical training may lead to more developed internal models that lead to stronger rhythmic expectations.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of studies comparing musicians and non-musicians are somewhat contradictory. Musicians have shown a greater effect of syncopation on groove ratings [25], stronger motor response to high groove music [26], and larger error-related neural response to rhythmic violations, compared to non-musicians [27]. Conversely, several studies have suggested that musical training has little or no effect on groove ratings [3,26] or leads to lower groove ratings [28].…”
Section: Introductionmentioning
confidence: 99%
“…Participants completed the survey once they had given informed consent. They answered a series of questions related to demographic data (age, musical expertise, gender, country of residence, musical taste; for details, see Senn et al, 2018). They were instructed to use quality headphones or external loudspeakers during the experiment and to carry the experiment out in a quiet room.…”
Section: Methodsmentioning
confidence: 99%
“…Music psychology defines the experience of groove more narrowly as listeners' inner urge to move in response to the music (Davies, Madison, Silva, & Guyon, 2013;Eaves, Griffiths, Burridge, McBain, & Butcher 2019;Madison, 2001Madison, , 2006Sioros, Miron, Davies, Gouyon, & Madison, 2014). Many studies additionally describe this inner urge as being pleasant (Cameron et al, 2019;Etani, Marui, Kawase, & Keller, 2018;Janata, Tomic, & Haberman, 2012;Lustig & Tan, 2019;Madison, 2003;Madison, Gouyon, Ullèn, & Hörnström, 2011;Matsushita & Nomura, 2016;Matthews, Witek, Heggli, Penhune, & Vuust, 2019; & Hoesl, 2018;Stupacher, Hove, & Janata, 2016;Witek, Clarke, Wallentin, Kringelbach, & Vuust, 2014).…”
Section: T He Term Musical Groove Was Originallymentioning
confidence: 99%
“…Another study found that participants synchronised their body movement more readily with low-and medium-syncopation music, than with highly syncopated music (Witek et al, 2017). Finally, a recent study on popular music drum patterns reports that syncopation is positively associated with groove in expert music listeners, but no effect was measured for non-musicians (Senn, Kilchenmann, Bechtold, & Hoesl, 2018).…”
mentioning
confidence: 97%